2016
DOI: 10.1016/j.jcv.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus epidemic in Brazil. I. Fatal disease in adults: Clinical and laboratorial aspects

Abstract: Background Zika virus (ZIKV) was first detected in Brazil in May 2015 and the country experienced an explosive epidemic. However, recent studies indicate that the introduction of ZIKV occurred in late 2013. Cases of microcephaly and deaths associated with ZIKV infection were identified in Brazil in November, 2015. Objectives To determine the etiology of three fatal adult cases. Study design Here we report three fatal adult cases of ZIKV disease. ZIKV infection in these patients was confirmed by cells cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 32 publications
6
90
0
2
Order By: Relevance
“…The risk of ZIKV infection has historically been restricted to tropical/subtropical regions, but the virus has now spread into the Southern US. Recent studies have demonstrated that ZIKV infects and is toxic to human neural precursors; however, the molecular mechanism is not precisely known (Azevedo et al, 2016; Cugola et al, 2016; Li et al, 2016; Mlakar et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The risk of ZIKV infection has historically been restricted to tropical/subtropical regions, but the virus has now spread into the Southern US. Recent studies have demonstrated that ZIKV infects and is toxic to human neural precursors; however, the molecular mechanism is not precisely known (Azevedo et al, 2016; Cugola et al, 2016; Li et al, 2016; Mlakar et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A small number of severe human clinical cases have reported thrombocytopenia, anemia, and hemorrhagic manifestations detected by serum chemistry and complete blood count (CBC) tests (38). To investigate ZIKV-associated disease in the absence of outward clinical signs, serum chemistry panels, CBCs, body temperature, and body weight data were evaluated (S1 and S2 Figs) .…”
Section: Resultsmentioning
confidence: 99%
“…What started as yet another tropical disease has ended up being a much more serious threat because of its association with neurologic complications. Based on our knowledge so far, an ideal ZIKV prophylactic or therapeutic agent will be required to satisfy various criteria such as,Prevent ADE for ZIKV infection in DENV-immune individuals and vice versa.Not increase the chances of developing/worsening GBS, which means that the use of live-attenuated vaccines may be ruled out until the cause of GBS is identified.Safe for use in pregnant population and immune-compromised individuals especially because persons with immunosuppression or autoimmune disorders are at a higher risk of developing severe disease (Azevedo et al 2016). …”
Section: Discussionmentioning
confidence: 99%